Rancang Bangun Alat Pengendali Pompa dan Pemantauan Batas Minimum Larutan Hara pada Metode Aeroponik Menggunakan Mikrokontroler ESP32 - Liza Safitri; Gunawan Prasetyo (LPPM Universitas Putera Batam, 2022)
System design is the activity of translating the results of analysis into software form and then creating the system or improving the existing system. Monitoring is the continuous assessment of the function of program activities in terms of scheduled use of data input. Aeroponics is a system of plant cultivation development by way of plant roots are periodically moistened with granules of fine nutrient solutions such as fog so that the roots of plants hang in the air so that the absorption of nutrients in the roots is more maximal. Nutrient solution is a nutrient that plants need to move the metabolism of the plant body. The nutrients needed by plants contain several elements that must be met, including the minimum limit of availability of nutrient solutions so as not to run out of nutrients and plants can develop properly. The nutrient solution that is applied to the roots of the plant has a certain time, so that the roots of the plant can always get the necessary nutrients. So that the control of the speeding pump is very necessary. To facilitate the control and monitoring of aeroponics systems, esp32 microcontrollers are required. The Esp32 microcontroller is an open-source Internet of Things platform that means it can be entered by programs according to needs. Esp32 is a microcontroller that has embedded wi-fi and Bluetooth and is compatible with arduino IDE. The tools built have a positive impact on hydroponic cultivation farmers, especially aeroponic methods. This tool is also very flexible because it can be used for small to large scale aeroponic cultivation for industry.